2016
DOI: 10.5194/acp-16-14937-2016
|View full text |Cite
|
Sign up to set email alerts
|

Wintertime organic and inorganic aerosols in Lanzhou, China: sources, processes, and comparison with the results during summer

Abstract: Abstract. Lanzhou, which is located in a steep alpine valley in western China, is one of the most polluted cities in China during the wintertime. In this study, an Aerodyne high-resolution time-of-flight aerosol mass spectrometer (HR-ToF-AMS), a seven-wavelength aethalometer, and a scanning mobility particle sizer (SMPS) were deployed during 10 January to 4 February 2014 to study the mass concentrations, chemical processes, and sources of submicrometer particulate matter (PM1). The average PM1 concentration du… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
69
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 87 publications
23
69
6
Order By: Relevance
“…4h) was also similar to that observed in megacities Crippa et al, 2013;210 Elser et al, 2015;Zhang et al, 2015b;Hu et al, 2016;Xu et al, 2016) and was characterized by two peaks around the mealtime hours, reflecting the influence of cooking emissions. However, the COA concentration in this study was much lower than that reported in megacities (e.g., peak concentration: 2.5 μg m -3 versus 14 μg m -3 in Beijing; Hu et al, 2016), suggesting much less cooking emissions at the rural site.…”
Section: Diurnal Patternssupporting
confidence: 65%
“…4h) was also similar to that observed in megacities Crippa et al, 2013;210 Elser et al, 2015;Zhang et al, 2015b;Hu et al, 2016;Xu et al, 2016) and was characterized by two peaks around the mealtime hours, reflecting the influence of cooking emissions. However, the COA concentration in this study was much lower than that reported in megacities (e.g., peak concentration: 2.5 μg m -3 versus 14 μg m -3 in Beijing; Hu et al, 2016), suggesting much less cooking emissions at the rural site.…”
Section: Diurnal Patternssupporting
confidence: 65%
“…Overall, the PM 1 mass is closely correlated (R 2 = 0.97) with that of SMPS particle volume during the entire campaign, with a linear regression slope of 2.86. This slope is significantly higher than the estimated average PM 1 density of 1.44 g cm −3 , which is calculated based on the measured particle compositions in this study and the assumed particle densities of 1.2 for organics, 1.78 for (NH 4 ) 2 SO 4 , 1.72 for NH 4 NO 3 , 1.52 for NH 4 Cl, and 1.8 g cm −3 for BC (Zhang et al, 2005b;Xu et al, 2016). This discrepancy is likely introduced by various factors, including different transmission sizes between HR-ToF-AMS and SMPS (up to ∼ 1.0 µm in D va for AMS vs. limited size range of 14.6-661.2 nm in D m for SMPS), rough calculation of PM 1 density using assumed composition densities and spherical shape without considering the particle porosity, as well as the use of the empirical and constant CE value of 0.5 in this study.…”
Section: Inter-comparisons Between Different Instrumentsmentioning
confidence: 52%
“…The O / C ratio (0.85) of BBOA in this study was quite a bit higher than BBOA factors identified at other urban/rural sites in previous studies Huang et al, 2011;Mohr et al, 2012;Sun et al, 2016;Xu et al, 2016), suggesting its long-range transport feature. This aged BBOA feature was similar with those obtained at other remote sites worldwide, such as a remote forest site in Finland (Raatikainen et al, 2010), a remote background site in Greece (Bougiatioti et al, 2014), and a national air quality background sites in southern China , where OA were generally highly oxidized.…”
Section: Organic Aerosol Source Apportionmentmentioning
confidence: 59%
“…The average O / C value in this campaign is within the typical O / C range of 0.28-0.56 previously observed under polluted urban environments in China (Huang et al, , 2012He et al, 2011;Xu et al, 2016b;Hu et al, 2016;Lee et al, 2013). The diurnal variation in O / C plotted in Fig.…”
Section: Source Apportionment Methodsmentioning
confidence: 87%